Bcl-2 Family Proteins Were Involved in Pseudolaric Acid B-Induced Autophagy in Murine Fibrosarcoma L929 Cells - Jinghua Yu; Xiangru Li; Shin-ichi Tashiro; Satoshi Onodera; Takashi Ikejima (Elsevier, 2008)
Pseudolaric acid B (PAB) exerted cytostatic activity on murine fibrosarcoma L929 cells. The cytostatic mechanism of PAB on L929 cells was investigated in this paper. At 36 h, after 80 μM PAB treatment, the inhibitory ratio was 65.37 ± 4.12%, and the MDC staining ratio was strongest in L929 cells. 3-Methyladenine (3-MA), an inhibitor of autophagy, inhibited the generation of autolysosomes induced by PAB. The expression of autophagy-associated Beclin 1 protein was up-regulated, and microtubule-associated protein light chain 3 I (LC3 I) was cleaved into LC3 II after 80 μM PAB treatment from 12 h. Therefore, it was concluded that PAB exerted a cytostatic effect on L929 cells through autophagy. However, 80 μM PAB treatment did not induce apoptotic body formation, but 3 mM 3-MA promoted apoptosis, so autophagy might inhibit apoptosis. PAB had no effect on mitochondrial membrane potential (MMP), but upregulated the expressions of Bax and Bcl-2. Immunoprecipitation analysis showed that PAB inhibited Bcl-2 binding with Beclin 1. Additionally, PAB inhibited the localization of Bax in mitochondria, but Bcl-2 still was in the mitochondria to sustain MMP. Meanwhile PAB promoted the phosphorylation of cytoplasmic Bcl-2. Therefore the phosphorylation of Bcl-2 in the cytoplasm and the mitochondrial location of Bcl-2 might be the reasons why PAB inhibited the binding of Bcl-2 and Beclin 1. Keywords:: autophagy, L929 cell, pseudolaric acid B (PAB), Bcl-2 family protein